PENEGAKAN HUKUM NETRALITAS PEGAWAI NEGERI SIPIL (PNS) - Hartini, Sri (Jurnal Dinamika Hukum, 2009)
Basically, the substance of democracy is the existence of role/active participation in the governance based on independence, equality and freedom. Somehow in new era, this strategic position of public servant was used by political party which finally makes political problems in the conception of law enforcement and makes confusedness to the role of public servant. Finally, the government make coherent regulation concerning with the neutrality in the public service law.  Arrangement of public service neutrality, arranged in article 3 sentence (2) and sentence (3) Law No. 43 Year 1999 and Government Regulation No. 37 Year 2004 concerning prohibition order of public servant becoming political party member and official member. The regulation only arranging concerning public servant becoming member and official member of political party, while public servant which was nonmember of political party, what exactly more loyal in political party not yet been arranged in that regulation. The regulation which straightening of neutrality arrange in  the preamble which public servant that impinge this regulation not yet arranged to collision, though sanction to this regulation was riffed as public servant, for public servant that becoming member and official member of political party.  Keyword: Neutralities, political party, law enforcement